As múltiplas faces da evasão na educação superior a distância: a experiência do curso de tecnologia em gestão ambiental do IFRN em dois pólos de apoio presencial - Dantas, Aleksandre Saraiva (2011)
This research presents a reflection on the dropout rates in higher education courses available through distance education in a context marked by deep changes in various spheres of society and by the uncontrolled growth of this educational method. For this, the object of analysis is related to the reality of students of Technology in Environmental Management offered by the Instituto Federal de Educação, Ciência e Tecnologia, Rio Grande do Norte (RN), Brazil, through the distance education in presence support poles located in Mossoró (RN) and Martins (RN). In this field research development several strategies of data collection are used, such as participant observation of reality; analysis of documents related to distance education and to the classes in Technology in Environmental Management; questionnaires answered by students who dropped the course. The results of such research enable us to say that the dropout rates in distance higher education is mainly referred to the consequences of a combination of aspects involved in the course development, personal difficulties faced by students during the period they attend the lessons and elements inherent in the context in which the course and students are inserted. Nevertheless there are specific situations in which the student may drop the program due to the influence of a single aspect, whether it is inherent in the development of the course, a personal situation, or even a factor determined by the context in which the course or the student belongs to